Proceedings of the 3rd Asia Pacific Management Research Conference (APMRC 2019) 2020
DOI: 10.2991/aebmr.k.200812.018
|View full text |Cite
|
Sign up to set email alerts
|

Towards the Qualified Human Resource: Internship Program at Leading Ex-LPTK Universities in Indonesia

Abstract: Internship becomes a way to grow human resource capabilities in terms of competencies on knowledge or practical and soft skills. Higher education institutions like universities as the organizers of an internship program certainly have some roles to produce capable, intelligent and professional workforce. Therefore, it is undeniable that a good internship program in university is an important stage in the development of quality human resources. Our research aims to uncover the description of the system of organ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…Most of the students' topics helped them up-skilling and re-skilling their knowledge in areas such as the Internet of Things, artificial intelligence, and augmented reality. Putri et al (2020) found that e-internships provide a platform for students to learn from various avenues like projects, workshops, lecture series, and company learning management systems. Komal explains:…”
Section: Nisha Another Respondent Said -mentioning
confidence: 99%
See 2 more Smart Citations
“…Most of the students' topics helped them up-skilling and re-skilling their knowledge in areas such as the Internet of Things, artificial intelligence, and augmented reality. Putri et al (2020) found that e-internships provide a platform for students to learn from various avenues like projects, workshops, lecture series, and company learning management systems. Komal explains:…”
Section: Nisha Another Respondent Said -mentioning
confidence: 99%
“…However, many companies, educators, and students inexperienced with online or virtual internships are hesitant to see the worth or advantage of such internships (Alawamleh and Mahadin, 2022;Agrati and Vinci, 2020;Szymanski et al, 2007). Further, several stakeholders are involved in an internship program, like university management, faculty groups, and industry, but most important is the student community (Putri et al, 2020). The present study attempts to answer a prevalent research question in the current times, "What is the experience of the student community during virtual internships"?…”
Section: Introductionmentioning
confidence: 98%
See 1 more Smart Citation
“…The internship is a program provided in the higher education curriculum to improve students' mental skills and readiness to work [1,2]. The internship program helps universities to collaborate with industry and also provides opportunities for students to study collaboratively in a real work environment [3].…”
Section: Introductionmentioning
confidence: 99%
“…And according to(DM Putri et al, 2020) internships can support professional human resources at work. Several researchers have carried out other research relevant to these findings.…”
mentioning
confidence: 99%